POTENSI KOMUNIKASI MATEMATIS SISWA DALAM POKOK BAHASAN JAJAR GENJANG DI SEKOLAH MENENGAH PERTAMA - Yanuarini, Aditya Agnes; Sugiatno, Sugiatno; Sayu, Silvia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This study aims to describe students potential in communicating mathematical ideas through drawings, tables, Cartesian diagrams and related symbol of parallelogram at Junior High School. The research method used is descriptive. The subjects were 28 students in grade VII SMPN 7 Sungai Raya. The result of the research shows that the tendency of students mathematical communication potential about the parallelogram,which is studied with the picture is more likely to be developed in mathematics learning compared to sudents mathematical communication through Cartesian diagram, table, and symbol. Another finding, the potential of students’ mathematical communication related to the area of parallelogram with tables, tends to be mare likely to bedeveloped in mathematics learning than the potential of students’ mathematical communication with images, symbol, and Cartesian diagram.Key words: Mathematical Communication, The Potential Of Mathematical Communication